Characteristics of vocal cues, facial action units, and emotions that distinguish high from low self-protection participants engaged in self-protective response to self-criticizing - Vráblová, Viktória; Halamová, Júlia (Frontiers in Psychology, 2025)
IntroductionSelf-protection, also called protective anger or assertive anger, is a key factor in mental health. Thus, far, researchers have focused mainly on the qualitative analysis of self-protection.MethodsTherefore, we investigated facial action units, emotions, and vocal cues in low and high self-protective groups of participants in order to detect any differences. The total sample consisted of 239 participants. Using the Performance factor in the Short version of the Scale for Interpersonal Behavior (lower 15th percentile and upper 15th percentile) we selected 33 high self-protective participants (11 men, 22 women) and 25 low self-protective participants (eight men, 17 women). The self-protective dialogue was recorded using the two-chair technique script from Emotion Focused Therapy. The subsequent analysis was performed using iMotions software (for action units and emotions) and Praat software (for vocal cues of pitch and intensity). We used multilevel models in program R for the statistical analysis.ResultsCompared to low self-protective participants, high self-protective participants exhibited more contempt and fear and less surprise and joy. Compared to low self-protective participants, high self-protective participants expressed the action units the following action units less often: Mouth Open (AU25), Smile (AU12), Brow Raise (AU2), Cheek Raise (AU6), Inner Brow Raise (AU1), and more often Brow Furrow (AU4), Chin Raise (AU17), Smirk (AU12), Upper Lip Raise (AU10), and Nose Wrinkle (AU9). We found no differences between the two groups in the use of vocal cues.DiscussionThese findings bring us closer to understanding and diagnosing self-protection.